1999
DOI: 10.1099/00222615-48-2-157
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibilities of Yersinia enterocolitica and Y. intermedia isolates from aquatic environments

Abstract: Of 37 Yersinia isolates from various aquatic environments, seven were I: enterocolitica and 30 I: intermedia. These isolates were biotyped, serotyped and tested for their susceptibility to 20 antibiotics. All I: enterocolitica isolates were of biovar 1; those of I: intermedia were distributed amongst four biovars (1, 2, 4 and 6). On the basis of combined biotyping and serotyping results, Y. enterocolitica isolates were distributed in five and X intermedia in 17 groups. With the exception of one Y. enterocoliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…The majority of the 35 strains isolated from food (74?3 %) were resistant to FOX, as well as AMP, CEF and CFZ. The resistance profile obtained is in agreement with previous studies, in which resistance to AMP and many cephalosporins is frequently observed Tzelepi et al, 1999;White et al, 2002;Stock & Wiedemann, 2003). In fact, the expression of b-lactamase enzymes A and B has already been associated with Y. enterocolitica, Yersinia intermedia and Yersinia frederiksenii (Stock et al, , 2000Tzelepi et al, 1999).…”
Section: Drug-resistance Profilesupporting
confidence: 91%
“…The majority of the 35 strains isolated from food (74?3 %) were resistant to FOX, as well as AMP, CEF and CFZ. The resistance profile obtained is in agreement with previous studies, in which resistance to AMP and many cephalosporins is frequently observed Tzelepi et al, 1999;White et al, 2002;Stock & Wiedemann, 2003). In fact, the expression of b-lactamase enzymes A and B has already been associated with Y. enterocolitica, Yersinia intermedia and Yersinia frederiksenii (Stock et al, , 2000Tzelepi et al, 1999).…”
Section: Drug-resistance Profilesupporting
confidence: 91%
“…In the present study, Bla-B, the inducible cephalosporinase, was detected unequivocally based on the characteristic flattening of inhibition zone around cefotaxime disc adjacent to the imipenem disc in all the strains (Table 1). Tzelepi et al [17] also reported detection of a broad spectrum penicillinase (Bla-A) and an inducible cephalosporinase (Bla-B) in all the thirty aquatic isolates of Y. intermedia . Our study extends this information further to indicate that Bla-A was also present in Y. intermedia isolated from clinical and non-clinical (pig/wastewater) sources.…”
Section: Resultsmentioning
confidence: 99%
“…For ceftazidime, the MIC 50 and MIC 90 were 512 mg/L and 1024 mg/L respectively, and for cefepime, the values ranged from 256–1024 mg/L. Contrary to these, relatively lower MICs of penicillins and cephalosporins have been reported for Y. intermedia and Y. frederiksenii isolated in other parts of the world [13,17,18]. This may be due to difference in the sources from which organisms were isolated or their geographical origin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, they are sensitive to a lower extent to the nalidixic acid, ampicillin, and amikacin (1,2,10,11). With regard to the tetracycline antibiotic, there were reports indicating diverse results through undertaking a set of different essays so far.…”
mentioning
confidence: 99%